Вища освіта України у міжнародному просторі: стрімкий розвиток чи можливий занепад - Давидов, П. Г.; Яворський, О. Ю. (НТУ "ХПІ", 2015)
У статті розглядаються питання глобалізації світу та зростаюча роль освіти у соціалізації людей та мобільності населення. Досліджуються сучасний стан та потенційні можливості освітньої галузі України у інтеграції до європейського освітньо-наукового простору.

The article discusses the globalization of the world and the increasing role of education in the socialization of people and mobility of the population. We study the current status and potential of the education sector in the integration of Ukraine into the European educational and scientific space.
Higher education Ukraine in international space: rapid development or decline possible
Keywords: ринок праці; освітньо-науковий простір; глобалізація; інтеграція; education; labor market; educational and scientific space